Trastornos psiquiátricos y su asociación con el ciberacoso en una muestra de adolescentes mexicanos - Yassel Flores-Rodríguez; Olga Martínez-Aguilar; Liliana Guadalupe Tapia-Guillen; Marco Antonio Solís-Bravo; Aymara Gatica-Hernández; José Juan Escoto-López; Tania Lucila Vargas-Rizo; Luis Alberto Salinas-Torres; Enrique Navarro-Luna; Lilia Albores-Gallo (Instituto Nacional de Salud Pública, 2020)
No disponible